Development of Teachers' Competencies for Sustainable Development in Kazakhstan: Pedagogical Approaches and Policy Implications - Mukhambetaliyeva, Zukhra; Uzakova, Assem; Fujii, Hiroki (Jurusan Pendidikan Teknik Elektro, 2026)
Objective: This article examines the pedagogical aspects of developing the professional competencies of chemistry teachers in the context of the Sustainable Development Goals (SDGs). In the face of global challenges, the teacher training system requires the integration of the principles of Education for Sustainable Development (ESD), aimed at fostering critical thinking, systematic analysis, and strategic planning. The article analyzes key teacher competencies necessary for the effective implementation of SDGs in the educational process, including systematic and critical thinking, anticipatory forecasting, normative and strategic competencies, as well as interdisciplinary collaboration skills. Particular attention is given to pedagogical models such as flipped learning, gamification, project-based, and interdisciplinary approaches that contribute to the professional development of chemistry teachers. The study substantiates the need for the implementation of innovative educational strategies aimed at developing environmental awareness, analytical skills, and research activities among future educators. Methodological aspects of integrating SDGs into chemistry teacher training curriculum, as well as international experience in this field, are explored. The research findings highlight the importance of a comprehensive approach to shaping the professional competence of chemistry educators, incorporating interactive teaching methods, digital technologies, project-based, and problem-oriented learning. The conclusion presents recommendations for optimizing the educational process to ensure teachers are prepared to integrate sustainable development principles into school chemistry education.